Prevalence of depression among Turkish University Students and related factors - Osman Gunay; Fatma Akpinar; Serpil Poyrazoglu; Haci Aslaner (Turkish Journal of Public Health, 2011)
Objective: This investigation was performed to determine the prevalence rate of depression and its correlates in students at Erciyes University. Method: A total of 1003 university students at the Medical, Theology and Engineering Faculties of Erciyes University in Kayseri, Turkey were included in the study. A socio–demographic questionnaire and a Beck Depression Inventory were completed by the students. An unpaired t test, a one way ANOVA test and a logistic regression analysis were used for the statistical analyses. Results: Total numbers of male and female students in the study group were similar and the mean age was 20.3±1.8. The mean Back Depression Inventory Beck Depression Inventory score was 11.3±8.6 points and prevalence rate of depression (Beck Depression Inventory ≥17) was 21.2%. The Mean Beck Depression Inventory score and depression prevalence were found higher among the students who had a physical illness, who were not satisfied with their body image or their faculty and who rated the economic level of their families as poor. Conclusion: It was concluded that approximately one–fifth of the students had depression. For the students, studying in a faculty which they are not satisfied is a major factor affecting depression. A better leadership should be provided for the students during the faculty selection procedure. Key Words: University student, depression, Beck Depression Inventory Üniversite öğrencilerinde depresyon prevalansı ve ilişkili faktörler Amaç: Bu çalışma, Erciyes Üniversitesi öğrencilerinde depresyon prevalansını ve bununla ilişkili faktörleri belirlemek amacıyla yapılmıştır. Yöntem: Erciyes Üniversitesinin Tıp, İlahiyat ve Mühendislik fakültelerinde okuyan toplam 1003 öğrenci araştırma kapsamına alındı. Öğrencilere sosyo-demografik anket ve Beck Depresyon Ölçeği uygulandı. Verilerin istatistiksel analizinde unpaired t testi, tek yönlü ANOVA testi ve logistik regresyon analizi uygulandı. Bulgular: Araştırma grubundaki erkek ve kız öğrenci sayıları birbirine yakındı ve yaş ortalaması 20.3±1.8 olarak belirlendi. Ortalama BDÖ puanı 11.3±8.6 ve depresyon prevalansı (Beck Depresyon Ölçeği puanı ≥17) % 21.2 bulundu. Fiziksel hastalığı olanlarda, beden görünümünden memnun olmayanlarda, okuduğu fakülteden memnun olmayanlarda ve ailesinin ekonomik durumunu kötü olarak belirtenlerde ortalama Beck Depresyon Ölçeği puanı ve depresyon prevalansı daha yüksek bulundu. Sonuç: Öğrencilerin yaklaşık beşte birinde depresyon vardır. Öğrencilerin, hoşlanmadığı bir fakültede okumaları depresyon sıklığını etkileyen en önemli faktörlerden biridir. Fakülte seçimi sırasında öğrencilere daha iyi rehberlik hizmeti sağlanmalıdır. Anahtar Kelimeler: Üniversite öğrencisi, depresyon, Beck Depresyon Ölçeği